Circulating immune complexes in syphilitic nephropathy. A case report. Issue 1 (February 1978) - Sølling, J; Sølling, K; Jacobsen, K U; Olsen, S; From, E
Abstract : A case of transient nephrotic syndrome caused by secondary syphilis is described. A renal biopsy was performed revealing subepithelial hump-like electron-dense deposits and fusion of epithelial foot-processes. Complement C1q-binding-activity and anticomplementarity were demonstrated in the blood, indicating the presence of circulating immune complexes. This strongly suggests that circulating immune complexes are significant in the immunopathogenesis of syphilitic nephropathy.